"That day no one spoke": Florida Puerto Ricans' Reaction to Hurricane María. (April 2020) - Capielo Rosario, Cristalís; Abreu, Roberto L.; Gonzalez, Kirsten A.; Cardenas Bautista, Elizabeth
We conducted two focus groups and four individual interviews to examine the experiences of Florida Puerto Rican adults ( N = 26) with secondary exposure to the devastation caused by Hurricane María. Results from our thematic analysis yielded four major themes and eight subthemes depicting responses to Hurricane María. Four major themes emerged across participant responses: 1) Participants' Experience with Hurricane María, 2) Participants' Negative Reactions to Hurricane María, 3) Participants Providing Support, and 4) Resilience and Growth. We also found that Florida Puerto Ricans' secondary stress reactions were influenced by Puerto Rico's political status and economic crisis. Results also indicated that participants experienced vicarious posttraumatic growth not only at the individual but also at the community level.